Retirement, Home Care and the Importance of Gender - Brändström, Anders; Sandström, Glenn (Historical Life Course Studies, 2021)
In recent decades elderly care policies in Sweden have been characterized by a marked shift from institutional care to home care. Previous research has highlighted how this has resulted in the elderly receiving care at a higher age and increased reliance on family and kin for providing care. Using register data for the entire Swedish population aged 65+ in 2016, we analyze how home care services in contemporary Sweden distribute regarding individual-level factors such as gender, health status, living arrangements, and closeness to kin. By far, the most critical determinants of receiving home care are age, health status, and whether the elderly are living alone or not. Although our results do not discard that access to kin have become more important, our results show that childlessness and geographical proximity to adult children play a minor role for differentials in the reception of home care. The main conduit for informal care instead takes the form of spousal support. Gender plays a role in how living arrangements influence the probability of receiving home care, where cohabiting women are significantly more likely to receive care than cohabiting men. We interpret this as a result of women, on average, being younger than their male partners and more easily adopting caregivers' roles. This gendered pattern is potentially explained by the persistence of more traditional gender roles prevailing in older cohorts.